Development of an Educational Game Based on Picture Quiz as an Interactive Learning Medium - Eldo, Handry; Najmi, Muazziss (Gameology and Multimedia Expert, 2025)
Educational games play a vital role in improving cognitive abilities and creativity in children and adults. This study discusses the development of a picture-based quiz game that integrates interactive learning elements with engaging visual challenges. The game, titled "Kuis Bergambar," allows players to answer quiz questions by first identifying images, fostering problem-solving skills and knowledge retention. Developed using the Game Development Life Cycle (GDLC), the game targets users aged 7-30 and is available on multiple platforms. Evaluation results show that this approach enhances engagement and cognitive performance compared to traditional quiz formats.